SOCIAL MEDIA MARKETING AND SALES PERFORMANCE OF CULINARY BUSINESSES IN KAWANGKOAN - Twice Seisy Oumuro Pinontoan; Paulus Kindangen; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
This study discusses about the roles of social media marketing in increasing sales performance in culinary businesses in Kawangkoan. Culinary businesses utilize social media as an online marketing tool to gain a satisfying market share. Currently social media is very easily accessed by anyone around the world, including culinary businessmen who use social media as a means of giving and sharing information about products offered to consumers online so that they are better known. The purpose of this research is to find out whether the roles of social media marketing can increase sales performance on culinary business. This research method is a qualitative methodology using a descriptive approach by utilizing secondary data originating from various literature such as books, journals/articles and homepages to access the latest information data and the sample used in this study is 15 respondents who run a culinary business and use social media. The results of this study indicate that Social Media Marketing provides good prospects for increasing sales performance in Culinary Businesses in Kawangkoan. Keywords: Social Media Marketing, Sales Performance, Culinary Business